IMPLEMENTATION OF QR CODES ON ICHIBAN SUSHI RESTAURANT'S DISH MENU ON ORDER TIME EFFICIENCY AND CUSTOMER SATISFACTION LEVEL - Firstarine Alberlianasari; Salma Nabilah; Safrina Dewi Rahmawati (Transpublika Publisher, 2022)
This research aims to find out how the QR code affects the efficiency of consumer ordering time and the level of consumer satisfaction with the QR code. This is a qualitative research which describes the QR code research on the Ichiban Sushi restaurant menu. Data collection techniques using observation and interviews. The research carried out on